1971
DOI: 10.1029/ja076i022p05252
|View full text |Cite
|
Sign up to set email alerts
|

Quiettime observation of a coherent compressional Pc-4 micropulsation at synchronous altitude

Abstract: During a magnetically quiet interval (1740–1850 UT), on February 14, 1967, the magnetic‐field intensity and energetic electron fluxes (E≈0.3–2.0 Mev) at ATS 1 exhibited coherent modulations having a frequency of 33.8 cph (period ≈106.5 sec) and a duration of approximately 40 oscillations. The electron fluxes and the magnetic field oscillated in phase. The field perturbation reached 8 γ (peak to peak) in the direction of the unperturbed geomagnetic field. The transverse component of the field perturbation was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Because the field line displacement is not a directly measurable quantity, one determines its symmetry from the associated magnetic field perturbation. An equatorial compressional Pc 4 wave observed by the ATS I geostationary satellite (magnetic latitude ~ 2 ø) exhibited properties similar to those reported by Hillebrand et al [1982], but whether the pulsation was a giant pulsation has not been discussed [Barfield et al, 1971;Lanzerotti and Tartaglia, 1972]. At the equator, for example, an odd-mode wave has a node of the transverse component and an antinode of the compressional component.…”
supporting
confidence: 54%
“…Because the field line displacement is not a directly measurable quantity, one determines its symmetry from the associated magnetic field perturbation. An equatorial compressional Pc 4 wave observed by the ATS I geostationary satellite (magnetic latitude ~ 2 ø) exhibited properties similar to those reported by Hillebrand et al [1982], but whether the pulsation was a giant pulsation has not been discussed [Barfield et al, 1971;Lanzerotti and Tartaglia, 1972]. At the equator, for example, an odd-mode wave has a node of the transverse component and an antinode of the compressional component.…”
supporting
confidence: 54%
“…However, if the perpendicular energy flow does exist, and it seems quite likely in the actual case, as pulsations are found down to low L values, the total power can be estimated. Ea = 4 mV/m and B• = 4 nT give a mean power density of 6 x 10 -• W/m 2, and if the area at geosynchronous distance, over which the wave is found, is roughly set to 6 x 10 a½ m •, equivalent to a belt at the equatorial plane extending, for example, 20 ø in latitude and 5 hours in longitude, we obtain a total power of 3.6 x 10 9 W. This is a considerable but not unrealistically large quantity and is comparable to results given by Greenwald and Walker [1980], who calculate a power dissipation from the wave field in a magnetospheric storm to be 6 x 109 W. Barfield et al [ 1971].…”
Section: Satellite Observationssupporting
confidence: 83%
“…On the other hand, the micropulsations observed on the ground are mostly torsional (Saito, 1969). A recent satellite observation by ATS-1 has, however, shown that a pure compressional oscillation of a period around 2 rain were observed which was observed at College, Alaska as a pure torsional oscillation (Barfield et al, 1971). There should exist some mode conversion from a compressional mode to a torsional one in somewhere.…”
Section: Discussionmentioning
confidence: 99%